Warming and oligotrophication cause shifts in freshwater phytoplankton communities. (25th June 2018) - Verbeek, Laura; Gall, Andrea; Hillebrand, Helmut; Striebel, Maren
Abstract: While there is a lot of data on interactive effects of eutrophication and warming, to date, we lack data to generate reliable predictions concerning possible effects of nutrient decrease and temperature increase on community composition and functional responses. In recent years, a wide‐ranging trend of nutrient decrease (re‐oligotrophication) was reported for freshwater systems. Small lakes and ponds, in particular, show rapid responses to anthropogenic pressures and became model systems to investigate single as well as synergistic effects of warming and fertilization in situ and in experiments. Therefore, we set up an experiment to investigate the single as well as the interactive effects of nutrient reduction and gradual temperature increase on a natural freshwater phytoplankton community, using an experimental indoor mesocosm setup. Biomass production initially increased with warming but decreased with nutrient depletion. If nutrient supply was constant, biomass increased further, especially under warming conditions. Under low nutrient supply, we found a sharp transition from initially positive effects of warming to negative effects when resources became scarce. Warming reduced phytoplankton richness and evenness, whereas nutrient reduction at ambient temperature had positive effects on diversity. Our results indicate that temperature effects on freshwater systems will be altered by nutrient availability. These interactive effects of energy increase and resource decrease have major impacts on biodiversity and ecosystem function and thus need to be considered in environmental management plans. Abstract : While there is a lot of data on interactive effects of eutrophication and warming, to date, we lack data to generate reliable predictions concerning possible effects of anthropogenic changes in the environment on community composition and functional responses. We set up an experiment to investigate the single as well as the interactive effects of nutrient reduction and gradual temperature increase on a natural freshwater phytoplankton community, using an experimental indoor mesocosm setup. Our results indicate that temperature effects on freshwater systems will be altered by nutrient availability.